Evaluation of Affective Aspects in the Implementation of Integrated Islamic Values Learning Model in Senior High Schools - Rindawan, Rindawan; Mujriah, Mujriah; Muhsan, Muhsan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to describe the affective domain of students in the implementation of an integrated Islamic value-based learning model at Rahmatullah Al Ma'arif Darek High School. The background of this study is based on the importance of education in shaping students' character through internalizing the values of honesty, responsibility, empathy, and discipline, which often receive less attention than the cognitive domain. The research method uses a quantitative descriptive approach with an evaluative design. Data were collected through a Likert scale questionnaire, teacher observations, and interviews with educators. The results showed that most affective indicators were in the Good to Very Good category, with the highest scores in the aspects of trustworthiness, politeness, and respect for teachers. Teacher observations reinforce these findings by demonstrating consistent positive student behavior within the learning context. However, empathy still needs to be strengthened through a collaborative and contextual approach. This conclusion suggests that Islamic values-based learning can significantly improve students' affective domains. This research has important implications for the development of a more systematic values-based curriculum and emphasizes the need for valid and standardized affective evaluation instruments. Recommendations for further research include the development of longitudinal evaluation instruments and more effective learning exploration strategies to foster students' social empathy.